Privacy-preserving frequent itemset mining in vertically distributed data using ElGamal encryption - Chung, Nguyễn Văn; Sự, Trần Đức (Journal of Science and Technology on Information security, 2023)
Abstract— Privacy-preserving data mining is increasingly receiving the attention of the research community, especially privacy-preserving frequent set mining, which is a topic that has been discussed a lot in recent times. In this paper, we propose a novel technique for privacy-preserving freuquent itemset mining in three party vertically distributed data. We show that the proposed technique is as efficient as the best existing protocols for performing the same task, and more secure than the most secured protocols with against collusion, 3 members joined the protocol the 2 members colluded not to reveal data of the other member.